Age‐related differences in self‐report and objective measures of cognitive function in older patients prior to chemotherapy - Inger Utne; Borghild Løyland; Ellen Karine Grov; Hege Lund Rasmussen; Ann Helen Torstveit; Steven M. Paul; Christine Ritchie; Kristina Lindemann; Ingvild Vistad; Claudia Rodríguez‐Aranda; Christine Miaskowski (Wiley, 2022)
Abstract Aim Evaluate for differences in demographic and clinical characteristics and subjective and objective measures of cognitive function (CF) between younger older adults (YOA, 60-69 years) and older adults (OA, ≥70 years). Design Cross‐sectional. Methods Older oncology patients (n = 139) completed subjective (Attentional Function Index, European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC) CF scale) and objective (Montreal Cognitive Assessment, Trail Making Test (TMT) A & B) measures of CF prior to chemotherapy. Data were analyzed using parametric and nonparametric tests. Results No differences were found between the two groups for any of the subjective or objective CF measures, except that OA patients had higher TMT B scores. Compared with the general population, OAs had significantly higher EORTC CF scores and YOAs had significantly worse scores for all of the objective tests. Clinically meaningful difference between group differences was found for the TMT B test.